Precise measurements of the wavelength in KrCl laser spectral region (222 nm) - Zubrilin, N.G.; Pavlov, I.A.; Baschenko, S.M.; Tkachenko, O.M. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2016)
The technique for precise measurements of wavelengths in the range around 222 nm (45030 cm⁻¹) has been presented. The reciprocal linear dispersion of the spectrometer was 0.529 Å/mm. The measurements were made in the second spectral order for a grating with 2400 lines/mm. Identification of emission lines of hollow cathode lamp (Fe) was made in the spectral range 4428…4452 Å. The wavelengths were measured for 32 identified lines in the spectrum. The mean square error of easurements is ∼0.0005 Å.